Implementasi Layanan Perizinan Berbasis Online Single Submission (OSS) dari Prespektif Risiko di Mall Pelayanan Publik pada DPMPTSP Manggarai Barat - Fitri Hilda; David B. W. Pandie; David Wilfrid Rihi; Nursalam Nursalam (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to describe the implementation of the risk-based OSS system and to identify the obstacles encountered in its implementation. This research employs a qualitative method with a descriptive approach. Data were collected through interviews, observation, and documentation, and were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The analytical framework is based on Charles O. Jones’ policy implementation theory, which includes the aspects of organization, interpretation, and application, and is examined from a risk management perspective.The findings indicate that the implementation of OSS-RBA at the MPP of West Manggarai has been relatively effective, particularly in facilitating the issuance of Business Identification Numbers (NIB) and business licenses for Micro and Small Enterprises (MSEs). However, several challenges remain, including limited understanding among business actors, the dependency of business actors on service officers, inadequate internet infrastructure, and human resource readiness. Therefore, strengthening staff capacity, enhancing public socialization, and improving technological infrastructure are necessary to ensure more effective and sustainable implementation.